HUBUNGAN EMOTIONAL EATING, CITRA TUBUH, DAN TINGKAT STRES DENGAN IMT/U REMAJA PUTRI DI SMK NEGERI 41 JAKARTA TAHUN 2022 - Jihan Juzailah, (2022)
Overweight problems in female adolescents can be caused by inappropriate eating behavior, one of which is emotional eating. Overweight can also be caused by stress or negative body perceptions. This can encourage adolescents to increase their food intake, so that if it's done continuously it'll have an impact on overweight. This study aims to determine the relationship between emotional eating, body image, and stress level with the BMI-for-age in female adolescents at SMK Negeri 41 Jakarta. This study used a cross-sectional design among 62 respondents determined by stratified random sampling technique. This study was conducted in May 2022. Data collected using The Dutch Eating Behavior Questionnaire-13 items (DEBQ-13), Figure Rating Scale (FRS), and Perceived Stress Scale-10 items (PSS-10). Relationship analysis performed using Chi Square test showed that there was no relationship between emotional eating (p value = 0, 642; p value > 0,05), body image (p value = 0,578; p value > 0,05), and stress level (p value = 1,000; p value > 0,05) with the BMI-for-age in female adolescents at SMK Negeri 41 Jakarta. It's necessary to conduct further studies related to factors that can influence the BMI-for-age, especially in female adolescents.